Learning Patterns and Their Implications in the Development of Students' Religious Character - Sri Jumini; Rahmiati Rahmiati; Rifqi Muntaqo; Abdul Majid; Yatim Md Nadrah; Winarto Winarto (Journal of Innovation in Educational and Cultural Research, 2025)
Indonesian education is experiencing an ethical crisis in all education lines. This study aims to identify learning patterns and the development of students' religious characters and determine the relationship between the two. This study uses a quantitative approach. The research sample was class VIII students of SMP Takhasus Al-Qur'an and SMP Al-Madina Wonosobo. Data collection used questionnaires, interviews, and observations. Data were analyzed using a correlation coefficient test to determine the relationship between the two variables. The study results showed that: 1) The learning patterns of both schools were the same, using differentiated learning, with individual, group, and guided learning patterns. 2) The religious character of SMP Takhasus Al-Qur'an students was 69%, in the low category. The religious character of SMP Al-Madina students was 82%, in the high category. 3) Both schools have a positive relationship between learning patterns and students' religious character. SMP Takhasus Al-Qur'an, by 0.159 or 15%. SMP Al-Madina, by 0.199 or 19%. This research has a good impact on creating learning patterns that can improve students' religious character.